2014
DOI: 10.1016/j.socscimed.2014.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Is breast truly best? Estimating the effects of breastfeeding on long-term child health and wellbeing in the United States using sibling comparisons

Abstract: Breastfeeding rates in the U.S. are socially patterned. Previous research has documented startling racial and socioeconomic disparities in infant feeding practices. However, much of the empirical evidence regarding the effects of breastfeeding on long-term child health and wellbeing does not adequately address the high degree of selection into breastfeeding. To address this important shortcoming, we employ sibling comparisons in conjunction with 25 years of panel data from the National Longitudinal Survey of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
151
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 53 publications
(74 reference statements)
3
151
1
7
Order By: Relevance
“…This includes both parenting characteristics and broad socioeconomic variables; all are partially heritable (23)(24)(25)(26)(27)(28). In the past decade, quantitative genetic research of this type has been extended to explore genetic and environmental contributions to correlations between environmental factors and children's outcomes (29)(30)(31)(32). Some new designs such as the children-of-twins designs make it possible to tease apart different types of genotype-environment correlation and identify environmental influences free of genetic confounds (33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…This includes both parenting characteristics and broad socioeconomic variables; all are partially heritable (23)(24)(25)(26)(27)(28). In the past decade, quantitative genetic research of this type has been extended to explore genetic and environmental contributions to correlations between environmental factors and children's outcomes (29)(30)(31)(32). Some new designs such as the children-of-twins designs make it possible to tease apart different types of genotype-environment correlation and identify environmental influences free of genetic confounds (33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…Some of these include how income and family structure impact routine medical and dental care provision for children (Berger 2004), the association between unwanted pregnancy and prenatal and postpartum maternal behaviors that adversely affect infant and child health (Joyce et al 2000), the relationship between dark and cluttered home environments and the incidence of home injuries among children (Mott 1999), the distance between a child's home and a hospital and the probability of utilizing preventive care (Currie and Reagan 2003), length of maternity leave and children's immunizations (Berger et al 2005), the effects of breastfeeding on long-term child health and well-being (Colen and Ramey 2014), various measures of economic disadvantage on intrauterine growth restriction ), household income histories, and changes in child depression levels (Strohschein 2005). Finally, a recent paper by Wolfe (2015) unpacked the components of socioeconomic status and found that children's health was more vulnerable to their families' wealth whereas adolescents' health was more sensitive to the current income of their families.…”
Section: Health Research Using the Nlsy Surveysmentioning
confidence: 99%
“…This result is consistent with the RCT, sibling-pair, and cross-population studies, which all suggest there is no effect of breastfeeding on mea-sures of obesity. 4,5,8 Most cohort studies of breastfeeding and obesity (largely from rich countries) may reproduce the same patterns of residual and unmeasured confounding. This is apparent when the RCT data were analyzed ignoring the randomized treatment assignment: no effect of the breastfeeding promotion intervention on infant growth in the RCT, but effects observed when the RCT was analyzed observationally (ie, as fed, rather than as randomized).…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%
“…5 However, sibling-pair comparisons show a much smaller effect of 0.22 higher (SE, 0.18) IQ scores comparing breastfed and not breastfed siblings. 8 Thus, the RCT, cohort, and crosspopulation studies suggest that breastfeeding raises IQ, but negligible effects are noted in sibling studies. Methods for evaluating health evidence give greater weight to RCTs.…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%